Optimizing Investments in Belarus for the National HIV Response - World Bank (World Bank, Washington, DC, 2016)
This report summarizes the findings of an allocative efficiency analysis on Belarus` national HIV epidemic and response conducted in 2014-15. The report addresses core questions for resource allocation such "How can HIV funding be optimally allocated to the combination of HIV response interventions that will yield the highest impact?" or "What level of investment is required to achieve national targets, if we allocate resources optimally?". The report describes epidemiological and HIV financing trends as well as identifies sub-populations, which are most affected by the epidemic. Based on this information, the optimized mix of interventions for minimizing new HIV infections and deaths is identified using mathematical modelling techniques. Belarus could increase the impact of its HIV program by reallocating funds to high-impact programs. It could enhance this impact by increasing the total funding available to the HIV response so that high-impact programs could be scaled up further. With optimized allocations of the same amount of funding available as in 2013 (US$19.7 million), over 2015–20, new HIV infections could be reduced by 7 percent and deaths by 25 percent. Doubling the investment in high-impact programs would require 148 percent of total 2013 spending (US$29.5 million). Compared to 2013 allocations, over 2015–20, the 148 percent investment would achieve a remarkable reduction in new infections by 43 percent and in deaths by 51 percent.